Numerical simulation and experimental corroboration of galvanic corrosion of mild steel in synthetic concrete pore solution. (October 2019) - Mohammadian, Armita; Rashetnia, Reza; Lucier, Gregory; Seracino, Rudolf; Pour-Ghaz, Mohammad
Abstract: Corrosion of reinforcing steel in concrete is one of the most prevalent deterioration mechanisms affecting reinforced concrete structures. While there have been significant advances in modeling the initiation stage of corrosion, corrosion kinetic models for predicting the rate of corrosion after depassivation of steel are scarce, and models with experimental corroboration under controlled experimental conditions are virtually nonexistent. Furthermore, the sensitivity of corrosion kinetic models to the uncertainty of their input parameters is not understood. The objective of the present work is to model active corrosion of steel in synthetic solution, experimentally corroborate the modeling approach under controlled conditions, and study the effect of uncertainty of the input parameters on the model predictions. To this end, a two-dimensional finite element method is used to solve the coupled system of Poisson-Nernst-Planck (PNP) equations subjected to electroneutrality constraint. To corroborate the modeling approach, the results of computations are compared against one-dimensional and two-dimensional galvanic corrosion of stainless/carbon steel in dilute and non-dilute NaCl electrolytes as well as two synthetic concrete pore solutions. The modeling parameters, including electrode polarization behaviors and electrolyte properties, are obtained experimentally. Monte Carlo simulations are used to understand the effect of uncertainty of polarization parameters on the predicted corrosion rate.